Copper catalyzed sequential arylation−oxidative dimerization of o-haloanilides: synthesis of dimeric HPI alkaloids. Issue 80 (24th August 2015) - Shen, Xianfu; Zhou, Yongyun; Xi, Yongkai; Zhao, Jingfeng; Zhang, Hongbin
Abstract : A copper catalyzed sequential arylation−oxidative dimerization reaction was developed as the key step for the synthesis of hexahydropyrroloindole alkaloids. Abstract : In this communication, we report a copper catalyzed sequential arylation−oxidative dimerization reaction as the key step for the synthesis of hexahydropyrroloindole alkaloids (+)-chimonanthine, (+)-folicanthine and (−)-calycanthine.